Inter-group relation and stress: a preliminary discussion - Habibah Artini Ramlie; Romzi Ationg; Easter Jawing (Institute for Promoting Research & Policy Development (IPRPD), 2019)
This paper presents a preliminary discussion about the inter-group relationship and its’ impact towards the psychological aspect as well as health in general. It also discusses what so-called relationship between inter-group relations and a worker’s psychological aspect which focuses on stress. Moreover, in brief, it also recommends and discusses ways on how the workers effectively deal with their stress during working time